Celecoxib suppresses autophagy and enhances cytotoxicity of imatinib in imatinib-resistant chronic myeloid leukemia cells. Issue 1 (December 2016) - Lu, Ying; Liu, Ling-Ling; Liu, Shou-Sheng; Fang, Zhi-Gang; Zou, Yong; Deng, Xu-Bin; Long, Zi-Jie; Liu, Quentin; Lin, Dong-Jun
Abstract Background Chronic myelogenous leukemia (CML) is a hematological stem cell disorder. Tyrosine kinase inhibitors (TKIs) are the standard treatments for CML, but a number of patients fail to respond effectively due to gene mutations. Celecoxib, a cyclooxygenase-2 (COX-2) inhibitor, has been shown to have anti-tumor effect on solid tumor whereas the anti-CML effect and its underlying mechanism have not been completely elucidated. Methods The cytotoxic effects of celecoxib and/or imatinib were evaluated by MTT assay. Cell cycle distribution was examined by propidium iodide (PI) assay. Apoptosis or necrosis was analyzed by Annexin-V/PI, Hoechst 33342 staining and Western blot assays. Autophagy suppression effect of celecoxib was examined by Western blot and LysoTracker probe labelling. Lysosensor probe labelling was used to detect the effect of celecoxib on the lysosomal function. Results In this study, we found that celecoxib had therapy efficacy in KBM5 and imatinib-resistant KBM5-T315I CML cell lines. Celecoxib caused significant cytotoxic effect in both cell lines, especially in KBM5-T315I cells exposed to celecoxib for 72 h. Moreover, celecoxib induced necrosis and apoptosis while inhibited autophagy in CML cell lines and patient samples. Furthermore, this study demonstrated that celecoxib prevented the autophagic flux by inhibiting lysosome function. Celecoxib was tested in combination with imatinib, demonstrating that celecoxib could strengthen the cytotoxicity of imatinib in imatinib-resistant CML cells. Conclusions These findings showed that celecoxib had therapy efficacy on CML cells. And it is first time to demonstrate that celecoxib is an autophagy suppresser and a combination of celecoxib and imatinib might be a promising new therapeutic strategy for imatinib-resistant CML cells.